Diversity of Mycobacterium tuberculosis Complex from Cattle Lymph Nodes in Eastern Cape Province. (10th April 2018) - Bhembe, Nolwazi Londiwe; Tanih, Godfred Ngu; Caine, Lesley-Anne; Pekana, Abongile; Govender, Patrick; Nwodo, Uchechukwu Uchechukwu; Okoh, Anthony Ifeayin; Mabinya, Leonard Vuyani; Green, Ezekiel
Abstract : Tuberculosis (TB) remains a major health challenge in South Africa and the condition in humans has been well researched and documented. However, investigations on the circulating Mycobacterium tuberculosis complex (MTBC) strains from cattle in the Eastern Cape Province of South Africa are insufficient. This study delineated the diversity of MTBC isolates from cows' lymph nodes. A total of 162 MTBC isolates, collected over a one-year period from cattle lymph nodes from two abattoirs, were submitted to spoligotyping and 12 MIRU-VNTR typing. The spoligotyping results were matched with isolates in the universal spoligotyping database (SITVIT2). Our study identified 27 spoligotype patterns, with 10 shared types assigned to five lineages: the East-Asian (Beijing) was predominant, 17.9%, and East-Asian (Microti) and Latin-American-Mediterranean S were the least detected with 0.6%. Spoligotyping showed a higher clustering rate of 82.1%, with the lowest being the Hunter-Gaston Diversity Index (HGDI) of 0.485; 12 MIRU-VNTR resulted in a clustering rate of 64.8%, showing a higher HGDI of 0.671. The results of this study show a high diversity of MTBC strains in the Eastern Cape Province and clustering rate, which indicates ongoing transmission in the province.